Depolarization causes the formation of a ternary complex between GlialCAM, MLC1 and ClC-2 in astrocytes: implications in megalencephalic leukoencephalopathy. (7th April 2017) - Sirisi, Sònia; Elorza-Vidal, Xabier; Arnedo, Tanit; Armand-Ugón, Mercedes; Callejo, Gerard; Capdevila-Nortes, Xavier; López-Hernández, Tania; Schulte, Uwe; Barrallo-Gimeno, Alejandro; Nunes, Virginia; Gasull, Xavier; Estévez, Raúl
Abstract: Megalencephalic leukoencephalopathy with subcortical cysts (MLC) is a rare type of leukodystrophy caused by mutations in either MLC1 or GLIALCAM. GlialCAM is necessary for the correct targeting of MLC1, but also for the targeting of the Cl - channel ClC-2. Furthermore, GlialCAM modifies ClC-2 functional properties in vitro . However, in vivo studies in GlialCAM -/- mice have shown that the modification of ClC-2 activity only occurs in oligodendrocytes, despite GlialCAM and ClC-2 being expressed in astrocytes. Thus, the relationship between GlialCAM, MLC1 and ClC-2 in astrocytes is unknown. Here, we show that GlialCAM, ClC-2 and MLC1 can form a ternary complex in cultured astrocytes, but only under depolarizing conditions. We also provide biochemical evidences that this ternary complex exists in vivo . The formation of this complex changes ClC-2 localization in the membrane and its functional properties. ClC-2 association with GlialCAM/MLC1 depends on calcium flux through L-type calcium channels and activation of calcium-dependent calpain proteases. Based on these studies, we propose that the chloride influx mediated by GlialCAM/MLC1/ClC-2 in astrocytes may be needed to compensate an excess of potassium, as occurs in conditions of high neuronal activity. We suggest that a defect in this compensation may contribute to the pathogenesis of MLC disease.